38.3k views
1 vote
Write f(x) = 2x^2 + 2x + 3 in factored form.

Write f(x) = 2x^2 + 2x + 3 in factored form.-example-1

1 Answer

6 votes

Answer:

Option b.

Explanation:

we know that

The formula to solve a quadratic equation of the form


ax^(2) +bx+c=0 i

s equal to


x=\frac{-b\pm\sqrt{b^(2)-4ac}} {2a}

in this problem we have


2x^(2) +2x+3=0

so


a=2\\b=2\\c=3

substitute in the formula


x=\frac{-2\pm\sqrt{2^(2)-4(2)(3)}} {2(2)}


x=\frac{-2\pm√(-20)} {4}

remember that


i=√(-1)

so


x=\frac{-2\pmi√(20)} {4}


x=\frac{-2\pm2i√(5)} {4}

simplify


x=\frac{-1\pm i√(5)i} {2}

therefore

In factored form the quadratic equation is equal to


2x^(2) +2x+3=2(x-(\frac{-1+i√(5)} {2}))(x-(\frac{-1-i√(5)} {2}))

User Chris Harris
by
4.6k points